Microfluidic buffer exchange for particle-based cell engineering and purification - Zhou, Yingying (2015)
Engineering cells with agent-loaded particles has been utilised to multiple research applications. It not only plays a significant role in bioimaging, which facilitates the monitoring of cell administration, but also boosts native cell properties that can be used in therapeutic applications. When loading cells with nanoparticles, the presence of unbound particles could cause problems such as: free bioimaging agents confound precise identification of labeled cells. Excessive free transformative agents can act on non-target cells, complicating therapeutic outcomes. Furthermore, excess particles can be a source of significant cytotoxicity. Therefore, we established a new microfluidic technology, Dean Flow Fractionation, to achieve efficiently remove unbound particles from both suspension and adherent cells. We demonstrated that Dean Flow Fractionation depletes more unbound particles than centrifugation and purified labelled cells can be continuously collected for downstream applications. We also illustrated that unbound particles are able to transfer bioimaging agents to non-target cells and transformative agents can affect cells’ physiology. This study suggests that Dean Flow Fractionation is a novel cell purification strategy and its high separation efficacy minimizes concerns regarding safety and false positive contrast. This allows particle-based cell engineering methods to fulfil its potential without bioimaging or off-target interference.